The 'plastic waste era'; social perceptions towards single-use plastic consumption and impacts on the marine environment in Durban, South Africa. (January 2020) - Van Rensburg, Melissa L.; Nkomo, S'phumelele L.; Dube, Timothy
Abstract: Plastics, one of the most abundant materials defining our society, are a major source of pollution. Plastics have redefined society's material culture and the artefacts that will be left behind. Plastic pollution in the ocean and in coastal environments is a growing concern which requires immediate attention. Single-use plastic is polluting coastal environments the world over, and this study focused on the issue within the context of Durban, South Africa. Advocating for behavioral changes from society remains a daunting task that requires an understanding of consumer perceptions towards single-use of plastics. This research paper aimed to gain an understanding of the social perceptions that beachgoers hold towards single-use plastic consumption in the coastal areas of Durban, South Africa. The sustainability science theoretical framework underpinned the research and the study used a mixed-methods approach to achieve the objectives. Questionnaires were used to accurately capture and reflect the perceptions towards single-use plastic consumption by the Durban beachgoers. The results from the study indicated that Durban beachgoers have a generally more negative perception towards single-use plastic; a high level of awareness towards their impacts on the environment; and a strong willingness to reduce their consumption of single-use plastic. Additionally, the results revealed a strong support towards potentially implementing a Container Deposit System (CDS) and a plastic bag ban in Durban to reduce the number of plastic bottles and bags polluting the coastal environment. Based on the findings, recommendations emphasized the need to incentivize reusable shopping bags; promote increased awareness and advocacy pertaining to the environmental concerns of single-use plastic; consider the implementation of a CDS; and further explore the potential of a plastic bag ban in Durban. This research can contribute towards developing adequate, appropriate strategies to address the issues of single-use plastic pollution. Highlights: Durban beachgoers have a more negative perception towards the consumption of single-use plastic. Durban beachgoers elicit a high level of awareness towards the environmental impacts caused by single-use plastic. Negative perceptions of single-use plastic consumption are linked to higher levels of environmental consciousness. The implementation of a Container Deposit System (CDS) would garner a high level of support in Durban. A plastic bag ban has a high likelihood of reducing single-use plastic consumption and coastal pollution in Durban.